ChemInform Abstract: Catalytic Metal‐Free Si—N Cross‐Dehydrocoupling. Issue 25 (24th June 2014) - Greb, Lutz; Tamke, Sergej; Paradies, Jan
Abstract The dehydrocoupling of hydrosilanes with anilines, carbazoles and indoles is reported.